INQUEST ON THE CONCEPTION BY HOSPITALITY MANAGEMENT STUDENTS OF THE TERM SUSTAINABILITY IN A STATE UNIVERSITY IN DANAO, CEBU, PHILIPPINES - Quiño, Looverville; Polinar, Mark Anthony; Delantar, Alexander Franco (Transpublika Publisher, 2024)
As people worldwide increasingly acknowledge the importance of sustainable practices to preserve resources and guarantee long-term environmental, economic, and social feasibility, it becomes imperative to understand how aspiring professionals in the hospitality industry perceive and interpret this concept. This study examines the understanding of the concept of sustainability among Hospitality Management students at a state university in Danao, Cebu. A descriptive-correlational approach was used to determine the respondents' demographic profile and degree of understanding regarding sustainability. Also, this study explores potential variations in student perceptions based on sex and academic strands. Forty-nine (49) first-year students were selected randomly to join the collection data and treated the data using frequency distribution, percentage, weighted mean, and ANOVA. The findings reveal that respondents perceived a high understanding of water and waste management. Also, there is a significant difference in how students from different genders and academic backgrounds conceptualize sustainability, particularly concerning energy and waste management practices. These results offer valuable insights into tailoring sustainability education within hospitality programs to address potential knowledge gaps and equip future professionals with a comprehensive understanding of sustainable practices in the industry.